2021
DOI: 10.3389/fnhum.2020.617222
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Leg Preference on Transient Characteristics of Body Sway During Single-Leg Stance: A Cross-Sectional Study

Abstract: Instrumented assessments of quiet-stance postural control typically involve recording and analyzing of body sway signal, most often the center of pressure (CoP) movement. It has been recently suggested that transient characteristics of body sway may offer additional information regarding postural control. In this study, we explored the relationship between whole-trial estimates of body sway (CoP velocity, amplitude, and frequency) and corresponding transient behavior indexes, as well as the effects of leg pref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(26 citation statements)
references
References 33 publications
4
22
0
Order By: Relevance
“…Reed et al (2020) reported that indexes of the transient behavior of postural sway were independent of the whole-trial estimates (in other words, they were not correlated with the whole-trial estimates), and were sensitive to age and vision elimination. In our subsequent studies, we confirmed the independence of transient indexes and the whole-trial variables, and demonstrated their sensitivity (albeit with small effect sizes) to leg preference (Kozinc and Šarabon, 2021a). Moreover, we found different transient behavior (i.e., quicker reduction of postural sway throughout the trial) in ballet dancers compared to young adults (Kozinc and Šarabon, 2021b).…”
Section: Introductionsupporting
confidence: 72%
See 2 more Smart Citations
“…Reed et al (2020) reported that indexes of the transient behavior of postural sway were independent of the whole-trial estimates (in other words, they were not correlated with the whole-trial estimates), and were sensitive to age and vision elimination. In our subsequent studies, we confirmed the independence of transient indexes and the whole-trial variables, and demonstrated their sensitivity (albeit with small effect sizes) to leg preference (Kozinc and Šarabon, 2021a). Moreover, we found different transient behavior (i.e., quicker reduction of postural sway throughout the trial) in ballet dancers compared to young adults (Kozinc and Šarabon, 2021b).…”
Section: Introductionsupporting
confidence: 72%
“…This implies that individuals with higher postural sway showed less stabilization (i.e., their sway was reduced less or was even increased throughout the trial). However, given that the associations were moderate, and the fact that four previous studies on larger sample sizes found no associations between whole-trial-estimates and corresponding indexes of transient behavior ( Reed et al, 2020 ; Kozinc and Šarabon, 2021a , b ; Kozinc et al, 2021 ), it is still reasonable to conclude that calculating and analyzing indexes of transient behavior can contribute new information to the traditional whole-trial analysis. Future studies investigating this topic should include correlational analysis to resolve this issue further.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In athletes, the preferred leg is commonly determined as the leg that the participant would use to kick a ball [ 5 , 14 , 15 ], which corresponds almost perfectly to handedness (the side of the preferred leg for writing and eating) [ 16 ]. However, other approaches, such as self-reported preferred leg for single-leg vertical jumping [ 14 , 17 ], have also been suggested. Due to the similarity of single-leg jump and single-leg landing, this approach could reveal clearer effects of leg preference in landing.…”
Section: Introductionmentioning
confidence: 99%
“…We determined the leg preference using two different approaches (i.e., kicking a ball and single-leg jumping) to investigate whether the method of preference determination affects the inter-leg differences. According to the available literature [ 13 , 16 , 17 ], we hypothesized that trivial to small differences between the legs will be detected in body sway tasks, regardless of the method of preference determination. Our second hypothesis was that larger differences will be confirmed for landing tasks when the leg preference will be determined based on single-leg jumping (in contrast to classification based on the preference to kick a ball).…”
Section: Introductionmentioning
confidence: 99%